PROSENTASE PEMBENTUKAN BUAH DAN BENIH PADA PERSILANGAN CABAI (Capsicum annum L.) VARIETAS SIRI AKIBAT PENGARUH WAKTU DAN SUHU PENYIMPANAN POLLEN - Widyana Rahmatika; Guntur Adi Wijaya (Universitas Islam Kadiri, 2016)
The purpose of this research was to understand the interaction effect of time and the pollen storage temperature on precentage of fruit formation dan seed on chilli (Capsicum annum L.) crossing. Research was conducted from April up to Juli 2016 at PT. BISI International Tbk. Jl. Koyo Mulyo Desa Kencong Kec. Kepung Kab.Kediri. The interaction between time and storage temperature of pollen on precentage of fruit formation dan seed on chilli (Capsicum annum L. ) crossing The first factor was pollen storage time (H) : H1 = Storage time 5 days H2 = Storage time 10 days H3 = Storage time 15 days The second factor is pollen storage temperature (S) : S1 = room temperature (24-27oC) S2 = refridgerator temperature (-3 oC) S3 = freezer temperature (-12 oC) Factorial experiment is composed at Randomized Block Design, with three replicants. The result of experiment showed there were interaction because of combination time and the pollen storage temperature to flower become fruit procentage, (%), harvest procentage (%), fresh weight fruit (gram), dry seed weight (gram). The best experiment was H1S2, time storage 5 days with temperature -3oC.